Feline Prostatic Carcinoma - de Oliveira, Mariana Pires; Barni, Brunna de Souza; Heinen Schuster, Lucas Antonio; Guimarães Gerardi, Daniel; Contesini, Emerson Antonio; Alievi, Marcelo Meller; Paravirini, Saulo Petinati (Acta Scientiae Veterinariae, 2019)
Background: Prostatic cancer is a rare condition in cats but should be included as a differential diagnosis whenever middle-aged cats present lower urinary tract signs, such as dysuria and hematuria. Abdominal ultrasound can indicate the disease, but fine-needle aspiration cytology and histopathology are necessary to establish the neoplastic origin and the therapeutic plan. Because of the limited data, no standard-of-care treatment or prognostic information exists in cats with prostate carcinoma. This report describes the clinical signs, diagnosis and surgical approach in a case of prostatic carcinoma in a cat. Case: A 6-year-old, intact male, domestic short-haired cat was presented with a 3-day history of dysuria, hematuria, inappetence, constipation, lethargy and prostration. On physical examination, the cat was in a very poor general condition and abdominal palpation revealed firm mass located caudally to the urinary bladder. The urinary bladder presented high repletion degree, while the large bowel was distended and presented soft faecal content. Blood count, serum biochemistry and urinalysis showed neutrophilic leukocytosis, hypoalbuminemia and high serum creatinine level, and severe hematuria, respectively. Abdominal ultrasound showed a mass located in the prostatic area with hypoechogenic and slightly heterogeneous parenchyma, measuring 3.3 x 3.0 cm. Echo-guided trans-abdominal fine-needle aspiration of the prostate was performed. Microscopically, the cells were round with basophilic cytoplasm, and had round to ovoid nuclei, dense chromatin and prominent nucleoli. Some cells were binucleated and mild anisocytosis and marked anisokaryosis were documented. These findings were compatible with malignant prostatic neoplasia. After initial clinical stabilization, the patient underwent an exploratory laparotomy for tumor resection. Cystotomy followed by pubic osteotomy was performed to access the tumor. Urethral anastomosis was necessary due to adherence of the neoplasm to adjacent structures. However, the patient died during the immediate postoperative period. No complications related to surgery were observed at necropsy. Tissue specimens were collected and stained by hematoxylin and eosin. Prostatic carcinoma was confirmed by immunohistochemistry tests using streptavidin-biotin-peroxidase complex method, and primary antibodies against vimentin, cytokeratin AE1/AE3 and 7. Discussion: Prostatic neoplams are rare in cats and clinical signs are suggestive of lower urinary tract disease, such as dysuria and/or hematuria, associated with tenesmus. Abdominal or rectal palpation seems to be essential to detect the prostatic enlargement. Ultrasound imaging was more sensitive than radiography, since it brings more information about structure, size, form and prostatic internal architecture. The patient’s serum creatinine value above the normal range for cats indicated partial urethral obstruction, due to neoplastic concentric growth. Echo-guided trans-abdominal fine needle aspiration cytology was an effective method to confirm neoplastic etiology. The advanced stage of the disease and poor clinical condition probably contributed to death at the immediate postoperative period, even though the surgical technique seemed to be appropriate as demonstrated at necropsy. Also, the immunohistochemistry tests allowed to confirm the diagnosis and excluded the main differential diagnoses, such as urothelial carcinoma and prostatic sarcomatoid carcinoma.